2005
DOI: 10.1177/230949900501300314
|View full text |Cite
|
Sign up to set email alerts
|

Terrible Triad of the Elbow—Role of the Coronoid Process: A Case Report

Abstract: Posterior dislocation of the elbow joint with fracture of both the radial head and coronoid process, the so-called 'terrible triad', is a complex and difficult-to-treat injury. We report a case of a 34-year-old man with terrible triad of the elbow and associated injuries secondary to a fall. The patient was treated with radial head osteosynthesis, resection of the coronoid process fragments, and stabilisation of the ulnohumeral joint by Kirschner wire transfixation. The sequence of treatment steps is provided.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Furthermore, conservative treatment regimens have been previously reported to bare unsatisfactory results, given that fracture site prone to redislocation. [18] Patients undergoing surgical treatment through a combined posterior lateral and anteromedial approach, however, showed increased fracture healing rate, improved elbow functioning, and decreased incidence of complications. [13] Similarly, another research demonstrated that surgical treatment regimens for terrible triad of elbow joint, such as radial head arthroplasty, repairing the coronoid or the joint capsule, and repairing the lateral ligament complex of the elbow, accomplished good results in majority patients, which was independent from treatment for radial head fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, conservative treatment regimens have been previously reported to bare unsatisfactory results, given that fracture site prone to redislocation. [18] Patients undergoing surgical treatment through a combined posterior lateral and anteromedial approach, however, showed increased fracture healing rate, improved elbow functioning, and decreased incidence of complications. [13] Similarly, another research demonstrated that surgical treatment regimens for terrible triad of elbow joint, such as radial head arthroplasty, repairing the coronoid or the joint capsule, and repairing the lateral ligament complex of the elbow, accomplished good results in majority patients, which was independent from treatment for radial head fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Coronoid fractures that are not amenable to fixation (because of size, comminution, or delay in treatment) may be reconstructed or treated non-operatively [3, 6-8, 11, 12, 14, 16, 19, 23]. Seijas et al, however, reported a case of persistent ulnohumeral subluxation requiring joint transfixation after excision of coronoid fragments in a terrible triad injury [20]. Other authors recommend against excision of bone fragments as they may be useful for callus formation [9].…”
Section: Discussionmentioning
confidence: 99%
“…In certain circumstances (e.g. low-energy falls from standing height and high energy accidents), posterior dislocation of the elbow may appear combined with fractures of the coronoid process and radial head in a complex injury termed as "terrible triad" (Seijas et al, 2005;Bohn et al, 2014). Isolated coronoid fractures, such as those caused by avulsion of the brachialis muscle, are rare (Gadgil et al, 2002) but have been reported in athletes, such as baseball pitchers (Akagi et al, 2000).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The latter bone changes were not observed in the case in discussion. In fact, the management of large fractures of the coronoid process constitutes a challenge for orthopaedic surgeons, sometimes requiring bone and soft tissues reconstruction (Ring, 2006;Seijas et al, 2005;Manidakis et al, 2012). It is highly possible that the severity of the coronoid fracture and the presence of trauma complications have led to some degree of disability in the right upper limb with a negative impact on the individual's daily activities.…”
Section: Differential Diagnosismentioning
confidence: 99%